2019
DOI: 10.3390/ijgi8110492
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Potential of VGI Metadata to Develop A Data-Driven Framework for Predicting User’s Proficiency in OpenStreetMap Context

Abstract: Volunteered geographic information (VGI) encourages citizens to contribute geographic data voluntarily that helps to enhance geospatial databases. VGI’s significant limitations are trustworthiness and reliability concerning data quality due to the anonymity of data contributors. We propose a data-driven model to address these issues on OpenStreetMap (OSM), a particular case of VGI in recent times. This research examines the hypothesis of evaluating the proficiency of the contributor to assess the credibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…They concluded that the most contributors of OSM "are hardly amateurs, but are professionals instead" (Yang et al, 2016). Rajaram and Manjula (2019) focused on determining user proficiency on OSM data based on contribution behaviour of users. They approximated that in India 17% of users were key contributors and 27% were inexperienced local users (Rajaram & Manjula, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the most contributors of OSM "are hardly amateurs, but are professionals instead" (Yang et al, 2016). Rajaram and Manjula (2019) focused on determining user proficiency on OSM data based on contribution behaviour of users. They approximated that in India 17% of users were key contributors and 27% were inexperienced local users (Rajaram & Manjula, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Rajaram and Manjula (2019) focused on determining user proficiency on OSM data based on contribution behaviour of users. They approximated that in India 17% of users were key contributors and 27% were inexperienced local users (Rajaram & Manjula, 2019). Zhang et al (2021) exploited evaluation-based weighted PageRank on OSM data for ranking of VGI contributor reputation.…”
Section: Introductionmentioning
confidence: 99%